Aproveitamento de efluentes na produção de biomassa algal: produtividade e remoção de nutrientes - Almeida, Herivanda Gomes de (2016)
Although it occurs interest and the expansion of cultivation of microalgae as renewable source for the production of biofuels and other bioproducts, the process is still considered expensive. The introduction of secondary effluent as a culture medium can offer better cost benefit for the production process. This study aimed to evaluate the microalgae Chlorella vulgaris and Scenedemus obliquus productivity when exposed to concentrations of 100% wastewater, to justify that alternative medium are promising for large-scale production and consequently to reduce spending on commercial fertilizers Another purpose was to evaluate the nutrients of removal efficiency by species. Cultivation in wastewater UASB reactors, a domestic source, other visceral source, was operated for ten days. The effluent used as a culture medium were derived from UASB reactors, a health source, Water and Sewage Company of Ceará-CAGECE, another waste of fish entrails after the removal of oil, the UASB LDFP / UFC. The domestic medium was higher in productivity, 330.2 mg.l-1.dia-1 for Chlorella vulgaris and 251.7 mg.l-1.dia-1 for Scenedemus obliquus. In effluent viscera species, in said order, showed productivity 85.79 ± 0.8 mg L-1.dia-1 and 60.99 ± 1.10 mg L-1 1.dia-in fourth and sixth day, respectively. The results showed cell density 116 x 106 and 23.75 x 106 cél.mL-1 Chlorella vulgaris in domestic and visceral substrate, respectively, and 22.7 x 106 and 10.6 x 106 cél.mL-1 Scenedesmus obliquus, respectively, for the same means. As a result of biomass production in the domestic effluent removal occurred around 88% of PT and PO4-3 and 100% of NTK the species. Chlorella vulgaris removed, also 65.7% of TOC and 48.7% of COD. Most removal PT in effluent viscera was 81.1%, post-Scenedesmus obliquus. The PO4-3 removed around 84%. Removing the nitrogen fractions did not exceed 75%, but was more significant removal of COD, holding Scenedesmus obliquus percentage of 87.4% and Chlorella vulgaris, in excess of, 91.5%.